Review: Modification of Nanocellulose as Conjugate of Infection-Causing Antibacterial Hydrogel - Anisa Anisa; Metik Ambarwati; Anggi Ayunda Triani; Indra Lasmana Tarigan (Jurnal Kimia Fullerene, 2021)
Infection is the process of entering and reproducing microorganisms such as bacteria, viruses, fungi, and parasites that cause tissue injury. Some of the common types of bacteria that play a role in wound infection are Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, and Staphylococcus epidermis. The antibacterial able to inhibit bacterial growth by inhibiting cell wall biosynthesis, increasing the permeability of the bacterial cytoplasmic membrane, and interfering with the normal bacterial protein synthesis. The aim of this review article is to conduct a study of nanocellulose as an antibacterial hydrogel conjugate. The method used is to summarize information from various recent journals related to nanocellulose, nanocellulose modification, nanocellulose-based hydrogels, and their application as antibacterial. Some journals from primary sources such as the PMC system (PubMed Central), National Library of Medicine (NIH), Science Direct, Elsevier, Nature, ACS Chemical Society, and several other sources. Nanocellulose consists of ÃŽÂ²-1, 4-glucose, and there are three hydroxyls active at the C2, C3, and C6 positions of the pyranose attachment. Nanocellulose can respond by the reaction of oxidation, esterification, or etherification, by adding a new functional group. Nanocellulose can become nanocellulose nanocrystals (CNC), cellulose nanofibers (NFC), and nanocellulose bacteria (BNC). Nanocellulose formulated in the form of hydrogels and combined with antibiotics will increase the effectiveness in reducing the risk of infection that is resistant to antibiotics.